2004
DOI: 10.1021/jp040442n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Surface Enhanced Raman Scattering (SERS) of Bacteria

Abstract: The surface enhanced Raman scattering (SERS) of a number of species and strains of bacteria obtained on novel gold nanoparticle (approximately 80 nm) covered SiO(2) substrates excited at 785 nm is reported. Raman cross-section enhancements of >10(4) per bacterium are found for both Gram-positive and Gram-negative bacteria on these SERS active substrates. The SERS spectra of bacteria are spectrally less congested and exhibit greater species differentiation than their corresponding non-SERS (bulk) Raman spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
434
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(461 citation statements)
references
References 57 publications
24
434
1
2
Order By: Relevance
“…Bacteria discrimination was first shown with Ag colloid SERS, showing discrimination at the strain level for E. Coli [319]. Differences in SERS spectra of various other bacteria species was also shown shortly after [320], and was shown to be potentially useful for bacteria 'barcoding' using multivariate statistics [321]. Different Ag NPs used for SERS were investigated for their antibacterial activity, and it was found that smaller (18 nm) were more toxic to bacteria than 80nm [322].…”
Section: Applicationsmentioning
confidence: 99%
“…Bacteria discrimination was first shown with Ag colloid SERS, showing discrimination at the strain level for E. Coli [319]. Differences in SERS spectra of various other bacteria species was also shown shortly after [320], and was shown to be potentially useful for bacteria 'barcoding' using multivariate statistics [321]. Different Ag NPs used for SERS were investigated for their antibacterial activity, and it was found that smaller (18 nm) were more toxic to bacteria than 80nm [322].…”
Section: Applicationsmentioning
confidence: 99%
“…Posteriormente, producto de la presencia de las bacterias y su interacción con el láser incidente, los pilares se alinean entre sí creando de este modo hot spots (zonas de aumento de campo electromagnético) que incrementan la intensidad de la señal Raman. Este mismo efecto ha sido utilizado para explicar el efecto SERS en otros estudios, utilizando sustratos diferentes [3,7,[16][17][18][19].…”
Section: Modos De Vibración Representativos De E Coliunclassified
“…Entre las más utilizadas se encuentran: evaporación al vacío, deposición electroquímica, pulverización catódica (sputtering) y plateo electroquímico [2][3][4]. Otra alternativa la constituyen los métodos basados en la nanoimpresión de metales sobre superficies de silicio, técnica conocida como nanolitografía.…”
Section: Introductionunclassified
“…Increasing in complexity, the detection and classification of pathogenic micro-organisms (viruses, bacteria, yeast, fungi and protozoa) (Alexander 2008;Jarvis & Goodacre 2008;Tripp et al 2008) and bacteria (Premasiri et al 2005;Evanoff et al 2006), as well as the study of complex tissues (Pinzaru et al 2008), have been largely improved through improvements in optical spectroscopy (i.e. spectral spatial resolution) and nanoparticle synthesis.…”
Section: Direct Sers Sensingmentioning
confidence: 99%